2020
DOI: 10.1111/bcp.14123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the UK Psychoactive Substances Act on awareness, use, experiences and knowledge of potential associated health risks of novel psychoactive substances

Abstract: Aims The risk of potential harms prompted the UK government to introduce the Psychoactive Substances Act in 2016. The aim of the present study was to evaluate the impact and effectiveness of this new legislation on patterns of novel psychoactive substance (NPS) awareness, use, experiences and risk awareness in a self‐selected sample of UK consumers to inform education and policy. Methods The Bristol Online Survey was advertised on the Bluelight drug forum and social media Facebook pages and University email be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The hidden-web drug marketplaces and crypto markets are increasingly being used for the anonymous sale of drugs, including NPS. Recent legislation, such as the May 2016 UK Psychoactive Substances Act, has been created to tackle NPS diffusion [8]. As commented in [9], although the Act may have achieved a reduction in UK-based online stores and offline retail stores, the easily tracked open-web drug transactions could be displaced by alternative routes such as street-level drug dealing or crypto markets.…”
Section: Monitoring the Nps-related Hidden/dark Areas Of The Web: Thementioning
confidence: 99%
“…The hidden-web drug marketplaces and crypto markets are increasingly being used for the anonymous sale of drugs, including NPS. Recent legislation, such as the May 2016 UK Psychoactive Substances Act, has been created to tackle NPS diffusion [8]. As commented in [9], although the Act may have achieved a reduction in UK-based online stores and offline retail stores, the easily tracked open-web drug transactions could be displaced by alternative routes such as street-level drug dealing or crypto markets.…”
Section: Monitoring the Nps-related Hidden/dark Areas Of The Web: Thementioning
confidence: 99%
“…The review showed that PSA enforcement led to the ban of NPS sale through headshops, has limited the sales and availability of NPS and reduced use, and as a result, there is evidence of reduction in health and social harms [8]. Deligianni and colleagues [9] evaluated the impact and effectiveness of the PSA 2016 through an updated survey in 2017 regarding NPS awareness, use, experiences and risk awareness and concluded that this regulation has not impacted on health risk awareness and motivations for NPS use in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Unforeseen consequences of the focus on how we deal with the challenges of the emergence of the large number of NPS is the potential increase in the availability and purity of classical illicit drugs, which may lead to greater harms from these substances . It is important that future studies in this field consider drug use in its entirety rather than focusing on just NPS or illicit drugs, which will enable us to truly understand the consequences of our response to the challenge of the NPS phenomenon.…”
mentioning
confidence: 99%
“…26,27 The impact of these novel mechanisms of controlling substances is not yet fully understood, but, as demonstrated in this themed issue and data from other sources, there is the potential that the UK Psychoactive Substance Act has reduced the availability, use, and associated harms of NPS. 21,[27][28][29] Unforeseen consequences of the focus on how we deal with the challenges of the emergence of the large number of NPS is the potential increase in the availability and purity of classical illicit drugs, 1 which may lead to greater harms from these substances. [28][29][30] It is important that future studies in this field consider drug use in its entirety rather than focusing on just NPS or illicit drugs, which will enable us to truly understand the consequences of our response to the challenge of the NPS phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation